Efeito da aplicação de boro, molibdênio e zinco no solo sobre a produção e conservação do alho - Ferreira de Novais, Roberto; Alves de Menezes Sobrinho, João (Revista Ceres, 2025)
The effect of soil applications of boron, molybdenum, and zinc on garlic bulb yield and preservation was studied in a soil from Patos de Minas, Minas Gerais, Brazil.